Monitoring independence in daily life activities after trauma in humanitarian settings: Item reduction and assessment of content validity of the Activity Independence Measure-Trauma (AIM-T) - Bérangère Gohy; Christina H. Opava; Johan von Schreeb; Rafael Van den Bergh; Aude Brus; Abed El Hamid Qaradaya; Jean-Marie Mafuko; Omar Al-Abbasi; Sophia Cherestal; Livia Fernandes; Andre Da Silva Frois; Eric Weerts; et al. (Public Library of Science (PLoS), 2022)
A standardized set of measures to assess functioning after trauma in humanitarian settings has been called for. The Activity Independence Measure for Trauma (AIM-T) is a clinician-rated measure of independence in 20 daily activities among patients after trauma. Designed in Afghanistan, it has since been used in other contexts. Before recommending the AIM-T for wider use, its measurement properties required confirmation. This study aims at item reduction followed by content validity assessment of the AIM-T. Using a two-step revision process, first, routinely collected data from 635 patients at five facilities managing patients after trauma in Haiti, Burundi, Yemen, and Iraq were used for item reduction. This was performed by analyzing inter-item redundancy and distribution of the first version of the AIM-T (AIM-T1) item scores, resulting in a shortened version (AIM-T2). Second, content validity of the AIM-T2 was assessed by item content validity indices (I-CVI, 0-1) based on structured interviews with 23 health care professionals and 60 patients in Haiti, Burundi, and Iraq. Through the analyses, nine pairs of redundant items (r≥0.90) were identified in the AIM-T1, leading to the removal of nine items, and resulting in AIM-T2. All remaining items were judged highly relevant, appropriate, clear, feasible and representative by most of participants (I-CVI>0.5). Ten items with I-CVI 0.5-0.85 were revised to improve their cultural relevance or appropriateness and one item was added, resulting in the AIM-T3. In conclusion, the proposed 12-item AIM-T3 is overall relevant, clear, and representative of independence in daily activity after trauma and it includes items appropriate and feasible to be observed by clinicians across different humanitarian settings. While some additional measurement properties remain to be evaluated, the present version already has the potential to serve as a routine measure to assess patients after trauma in humanitarian settings.